Development of e-Modules Based on Integrated Guided Inquiry TPACK (Technological Pedagogical Content Knowledge) on Chemical Equilibrium Material - Patricia Simatupang; Nora Susanti; Sardes Yosua Silaban (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2025)
This research aims to produce an electronic module (e-module) based on the Guided Inquiry model with the TPACK approach on chemical equilibrium materials. The research method is the Research and Development (R&D) method with the Thiagarajan 4D model consisting of 4 stages, namely define, design, develop and disseminate. The instruments used were in the form of needs analysis interview sheets, student characteristics questionnaires, validation sheets by material and media experts, and teacher and student response questionnaires. The e-module is declared valid after being validated by 3 lecturers and 3 media expert lecturers. The results of the validation of the e-module by material experts obtained a feasibility percentage of 88% with the criterion of